2020
DOI: 10.3390/d12090341
|View full text |Cite
|
Sign up to set email alerts
|

Raccoon Vigilance and Activity Patterns When Sympatric with Coyotes

Abstract: Nonconsumptive effects of predators potentially have negative fitness consequences on prey species through changes in prey behavior. Coyotes (Canis latrans) recently expanded into the eastern United States, and raccoons (Procyon lotor) are a common mesocarnivore that potentially serve as competitors and food for coyotes. We used camera traps at baited sites to quantify vigilance behavior of feeding raccoons and used binomial logistic regression to analyze the effects of social and environmental factors. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 62 publications
2
14
2
Order By: Relevance
“…We detected several trends in marten and fisher vigilance unrelated to our hypothesis. The reduction in vigilance for martens feeding in pairs is consistent with the hypothesis that group vigilance can partially compensate for individual vigilance 6 , 23 , 36 . However, because > 95% of marten visits were solitary individuals, foraging in groups is not likely an important risk response for martens.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We detected several trends in marten and fisher vigilance unrelated to our hypothesis. The reduction in vigilance for martens feeding in pairs is consistent with the hypothesis that group vigilance can partially compensate for individual vigilance 6 , 23 , 36 . However, because > 95% of marten visits were solitary individuals, foraging in groups is not likely an important risk response for martens.…”
Section: Discussionsupporting
confidence: 85%
“…Though statistical support was marginal, our results suggest that recent and intense fisher site use had a larger effect on marten vigilance. Other studies have generally found no vigilance response of free-ranging mesocarnivores to the presence of dominant carnivores 22 , 23 , although experimental studies found increased vigilance of mesocarnivores in response to presence and scent cues of dominant carnivores 24 . Our results provide evidence that mesocarnivore vigilance can be influenced by dominant carnivore presence in a wild population.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Alternatively, recall should be optimized if processing time is limited and every image of an animal is not essential for the global analysis. Optimizing recall is ideal for a general survey of common, easily identified animals (e.g., Chitwood et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Telemetry studies of raccoons have found some evidence of mortality due to coyotes, but only as a rare occurrence (Gehrt and Clark 2003;Prange et al 2003). In North Carolina, the temporal use of coyotes and raccoons largely overlapped and that raccoons overall exhibited low levels of vigilance, indicating low levels of fear from coyotes (Chitwood et al 2020).…”
Section: Introductionmentioning
confidence: 99%